2009
DOI: 10.1002/mde.1455
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous timing in a mixed duopoly: price competition with managerial delegation

Abstract: We introduce a managerial delegation contract into the mixed duopoly model and examine its influence on price setting in a mixed duopoly in the context of the endogenous-timing problem. We obtain the result that owners of a public and a private firm prefer to delay the setting of the prices of their products as much as possible. Thus, in equilibrium, the firms choose their prices simultaneously in the latter stage of the game. This is in contrast to the findings of the entrepreneurial case, according to which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
18
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 22 publications
(49 reference statements)
2
18
1
1
Order By: Relevance
“…Bárcena‐Ruiz () analysed both in a private and mixed duopoly under price competition whether owners of firms prefer to decide for their managers’ bonuses sequentially or simultaneously (thus neglecting the timing game by managers in the product market) and showed that, in a private duopoly, if one firm is the leader in the managerial contract the other firm prefers to be the follower and thus in equilibrium firms’ owners decide such contracts sequentially. By contrast, Nakamura and Inoue (), focusing on the timing game by managers at the market stage in a mixed firms context, obtained the result that owners of a public and a private firm prefer to delay the price setting of their products as long as possible and thus, in equilibrium, the firms choose their prices simultaneously.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Bárcena‐Ruiz () analysed both in a private and mixed duopoly under price competition whether owners of firms prefer to decide for their managers’ bonuses sequentially or simultaneously (thus neglecting the timing game by managers in the product market) and showed that, in a private duopoly, if one firm is the leader in the managerial contract the other firm prefers to be the follower and thus in equilibrium firms’ owners decide such contracts sequentially. By contrast, Nakamura and Inoue (), focusing on the timing game by managers at the market stage in a mixed firms context, obtained the result that owners of a public and a private firm prefer to delay the price setting of their products as long as possible and thus, in equilibrium, the firms choose their prices simultaneously.…”
Section: Introductionmentioning
confidence: 96%
“…Importantly, the scant early literature in this field (i.e. Lambertini, ,b; Nakamura and Inoue, ; Bárcena‐Ruiz, ) treated wages as exogenous, thereby abstracting from the important feature of unionisation of oligopoly industries. Indeed, Lambertini () addressed the issue of timing in a game between managerial firms, showing that delegation drastically modifies the owners’ preferences concerning the distribution of roles, as compared with the setting where firms act as pure profit‐maximisers; Lambertini () assumed that firms can choose not only whether to move early or delay as long as possible at the market stage, but also whether to act as quantity or price setters as well as whether to be entrepreneurial or managerial.…”
Section: Introductionmentioning
confidence: 99%
“…The use of incentive contracts as strategic variables in mixed markets is investigated, among others, by Barros () in a quantity setting framework and by Nakamura and Inoue () in a price setting framework.…”
mentioning
confidence: 99%
“…Subsequently, White (2001) paid attention to the strategic benefits resulting from managerial incentive contracts of both the public and private firms under complete information 6 . Furthermore, Nakamura and Inoue (2007, 2009) considered the endogenous timing problem in a mixed duopoly where the separation between ownership and management is observed in each firm in the context of quantity competition and price competition, respectively 7 . Although the above papers considered a situation where owners delegate to managers the decision of selecting strategic variables in the market through FJSV contracts, when multiple strategic variables other than delegation parameters need to be selected within managerial firms, an owner may choose one variable and the corresponding manager may choose another.…”
Section: Introductionmentioning
confidence: 99%